Biomechanical Analysis of Concentration and Coordination on The Accuracy in Petanque Shooting (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2019)
The purpose of this study was to determine the relationship between concentration and coordination on the accuracy of petanque shooting. This study using quantitative methods with survey and measurement test. Total subjects were 16 petanque athletes with the mean age (21.3 Â± 6.5 ) and all samples full fill the inform consent. Data analysis used multiple correlation with SPSS version 22 to measure concentration and coordination in petanque shooting. The result of concentration test in points 15-16 and 17-18 each in samples, points 13-14 and 19-21 respectively 3 samples and 11-12 points was 2 samples. The results of hand-eye coordination test in point 13-14 was 5 samples. Point 9-10, 11-12, and 15-16 were 3 samples each, and point 17-18 was 2 samples. Shooting test results found that point 19-21 was 5 samples, points 16-18 and 28-30 were 4 samples each, point 22-24 was 3 samples and point 25-27 no sample got that point. The conclusion found that there was relation between concentration and coordination in the shooting accuracy on petanque athletes achievement. Biomechanical analysis was used to analyze shooting movement to the top performance. Athletes who had good concentration and coordination can be confirmed to control the game and athletes who had low shooting value can improve concentration and coordination with focus on the intensive and ongoing training.